Vig, Albanien. Das spätantike Kastell und seine Umgebung. Die Arbeiten im Herbst 2018 - Oettel, Andreas; Hoxha, Gëzim (e-Forschungsberichte des DAI, 2020)
Since its discovery at the beginning of the 20th century, the location of the late ancient castrum of Vig in a wide river valley surrounded by mountains has given rise to speculation about its function. Protection from mountain tribes, the role as a station, and the organisation of ore mining were discussed. The last campaign of the project in autumn 2018 has been devoted primarily to these issues. Although copper deposits were found in the fort’s immediate vicinity, they apparently hadn’t mined here in ancient times. The castrum probably served to secure the nearby via Lissus – Naissus as well as the mountainous hinterland of the Zadrima plain.